Initial Results From the Oman Drilling Project Multi‐Borehole Observatory: Petrogenesis and Ongoing Alteration of Mantle Peridotite in the Weathering Horizon. Issue 12 (20th December 2021) - Kelemen, Peter B.; Leong, James A.; Carlos de Obeso, Juan; Matter, Jürg M.; Ellison, Eric T.; Templeton, Alexis; Nothaft, Daniel B.; Eslami, Alireza; Evans, Katy; Godard, Marguerite; Malvoisin, Benjamin; Coggon, Jude A.; et al.
Abstract: The Oman Drilling Project "Multi‐Borehole Observatory" (MBO) samples an area of active weathering of tectonically exposed peridotite. This article reviews the geology of the MBO region, summarizes recent research, and provides new data constraining ongoing alteration. Host rocks are partially to completely serpentinized, residual mantle harzburgites, and replacive. Dunites show evidence for "reactive fractionation, " in which cooling, crystallizing magmas reacted with older residues of melting. Harzburgites and dunites are 65%–100% hydrated. Ferric to total iron ratios vary from 50% to 90%. In Hole BA1B, alteration extent decreases with depth. Gradients in water and core composition are correlated. Serpentine veins are intergrown with, and cut, carbonate veins with measurable 14 C. Ongoing hydration is accompanied by SiO2 addition. Sulfur enrichment in Hole BA1B may result from oxidative leaching of sulfur from the upper 30 m, coupled with sulfate reduction and sulfide precipitation at 30–150 m. Oxygen fugacity deep in Holes BA3A, NSHQ14, and BA2A is fixed by the reaction 2H2 O = 2H2 + O2 combined with oxidation of ferrous iron in serpentine, brucite, and olivine. fO2 deep in Holes BA1A, BA1D, and BA4A is 3–4 log units above the H2 O‐H2 limit, controlled by equilibria involving serpentine and brucite. Variations in alteration are correlated with texture, with reduced, low SiO2 assemblages in mesh cores recording very low water/rock ratios, juxtaposed with adjacent veins recording much higher ratios. The proportion of reduced mesh cores versus oxidized veins increases with depth, and the difference in fO2 recorded in cores and veins decreases with depth. Plain Language Summary: The Oman Drilling Project developed a "Multi‐Borehole Observatory" (MBO) in an area of active weathering of tectonically exposed peridotite, to study the geochemistry, mechanics, and hydrology of peridotite alteration, which modifies the mineralogy, composition, density, and rheology of mantle lithologies, creates and sustains plate boundaries, and forms dramatic redox gradients. In turn, these redox conditions support a unique subsurface microbial ecosystem, form free H2 gas, facilitate methane generation, and potentially play a role in the origin of life on this and other planets. This paper provides an overview of the geology of the area within and surrounding the MBO, a summary of recent research on core and fluids from three new cored boreholes and four new rotary boreholes in the MBO, together with older Omani water monitoring well NSHQ14, and new data and calculations constraining ongoing peridotite alteration in this area. We constrain the igneous history of the mantle rocks, the extent to which they have been hydrated, carbonated, and oxidized. Highlights include new hypotheses on mechanisms of shallow sulfur depletion and deeper enrichment, and new insights into the interaction of water and minerals that controls the partial pressures of oxygen and hydrogen in this important geochemical environment. Key Points: Ongoing alteration decreases in intensity with increasing depth below the present erosional surface Sulfur is accumulating in a supergene enrichment zone from 30 to 150 m below the present erosional surface Deep oxygen fugacity is fixed by H2 gas saturation = plus ongoing oxidation of Fe 2+ in three holes and serpentine‐brucite equilibria in four holes